Estudio de pre factibilidad para la instalación de un taller de confección de prendas de vestir para niños en la empresa Vitotex E.I.R.L. - Giron Llanos, Gonzalo (2010)
The products to be developed in this research work are t-shirt type polo shirts, polo shirts with dress collars and flannel shirts. These products are aimed at children between 2 and 14 years of age in Metropolitan Lima. As a result of this study, a sufficiently large market was identified, made up of children between 2 and 14 years of age in the department of Lima who will require t-shirt type polo shirts, polo shirts with dress collars and flannel shirts. The grand total of children in Lima and the Constitutional Province of Callao is being considered. 350,247 t-shirt type polo shirts, 139,405 polo shirts with dress collars and 155,636 flannel shirts will be sold in the first year, making a total sale for all products of US $3,341,719. The total investment for the project is US$ 1,329,723. This investment will be 44% financed by shareholders and the rest through bank loans, which will be paid in 4 years. Finally, an economic and financial analysis of the project was made, where we demonstrated its feasibility with a NPV of US $ 4,729,829 and an IRR of 86.86%.